Wound Care in Burn Patients - Orhan Çizmeci; Samet Vasfi Kuvat (Galenos Yayinevi, 2011)
Wound care in one of the most important prognostic factors in burn victims. Open wound carries risks for infection due to hypothermia, protein and fluid losses. In addition, unhealed wounds are the major risk factors for acute-subacute or chronic complications in burn patients. Although no exact algorithm exists for open wound treatment, early escarectomy or debridement together with grafting is the best option. Ointments together with topical epithelizing agents without dressings are genereally adequate for first-degree burns. However, topical antibacterial agents are usually required for second to third-degree wounds. Standart treatment for the open wound without epithelization is autologous skin grafting. In cases where more than 50% of the skin surface in affected, autologus donor skin may not be enough. For these cases, epidermal cell culture in vitro may be used. Mesenchymal stem cell applications which have immunosupressive effects should be utilized in cases where cells need to be prepared as allografts. (Journal of the Turkish Society intensive Care 2011; 9 Suppl: 51-4)